The Role of the External Auditor in the Disclosure of Fraudulent Management Practices Applied to the Office of the National Auditor in Sudan - Takriti, Tamara Mowafaq (Finance and Business Economies Review, 2019)
The study dealt with the role of the external auditor in the detection of fraudulent management practices by applying to the National Audit Bureau. The study aimed at finding out the responsibility of the external auditor to detect mistakes and fraud. The following hypotheses were tested for validity of the following hypotheses: There is a statistically significant relationship between the external auditor and fraudulent management practices. There is a relationship between the fraudulent practices in the financial reports and the revenue measurement field. The study reached several conclusions, the most important of which is the responsibility of preventing fraud and manipulation In the financial statements on the management of the entity. The External Auditor is morally and legally responsible for disclosing the manipulation of the outcome accounts during the performance of the audit process under the Stock Exchange and Equity Laws